Marketing in the fashion industry: abilities as well as developmental characteristics. - Qoriyeva Shakhlo Abdufarruh qizi (Genius Publishing Group, 2023)
The article considers marketing strategies in the fashion society, and in addition, the priority trends in the formation of popular business.
Keywords: popularity; fashion marketing; advertising communications